2022
DOI: 10.3390/pharmaceutics14081609
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Reduces Short- and Long-Term High Glutamate Release after Severe Traumatic Brain Injury and Improves Functional Recovery

Abstract: This study aimed to determine if orally administered cannabidiol (CBD) lessens the cortical over-release of glutamate induced by a severe traumatic brain injury (TBI) and facilitates functional recovery. The short-term experiment focused on identifying the optimal oral pretreatment of CBD. Male Wistar rats were pretreated with oral administration of CBD (50, 100, or 200 mg/kg) daily for 7 days. Then, extracellular glutamate concentration was estimated by cortical microdialysis before and immediately after a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Current studies of CBD's effects on TBI suggest that CBD dosing and achieved concentrations are critical for achieving therapeutic benefits [e.g., ( 56 )]. Other characteristics such as method of administration [e.g., ( 13 )], duration of exposure, and temporal proximity to the TBI [e.g., ( 12 )] further complicate efforts for achieving a clear understanding of optimal therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current studies of CBD's effects on TBI suggest that CBD dosing and achieved concentrations are critical for achieving therapeutic benefits [e.g., ( 56 )]. Other characteristics such as method of administration [e.g., ( 13 )], duration of exposure, and temporal proximity to the TBI [e.g., ( 12 )] further complicate efforts for achieving a clear understanding of optimal therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the time course of CBD's efficacy will be a critical experimental consideration moving forward. There is currently insufficient evidence to draw any definitive conclusions because in many cases, CBD is administered prior to the primary injury [e.g., ( 12 )], after [e.g., ( 13 )], or both before and after [e.g., ( 56 )], and often not compared across administration period. Pretreatment may lead to lower mortality rates and improved sensorimotor function ( 12 ), but targeting at least some of CBD's mechanisms, like the ECS, within a “window of opportunity” of at least 15 min following the primary injury may also confer substantial neuroprotective benefits ( 124 ).…”
Section: Cbd's Neuroprotective Potential In Tbimentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment was administered 7 days a week for 3 weeks (Figure 1). Treatment dose and duration were chosen based on previous studies on different cognitive-assessment models with oral administration of CBD (41)(42)(43)(44)(45). Furthermore, we have performed a pilot study assessing doses of 2,5 mg/kg, 10 mg/kg, and 50 mg/kg, to which 50 mg/kg showed most significant positive results (data not shown).…”
Section: Experimental Groups and Dietmentioning
confidence: 99%